Implementation of Biology learning bedia Based on Augmented Instruction Reality to improve student learning outcomes on plant cell structure material - Maharani, Diana Eka; Sugianto, Sugianto; Subkhi, Nur (Nashir Al-Kutub Indonesia, 2024)
The results of a preliminary study at a junior high school in Indramayu Regency, particularly among seventh-grade students, indicate that there are still students who are less interested in studying biology, especially regarding the topic of plant cell structure. Many students struggle to memorize the various organelles of plant cells and their functions, which impacts their academic performance. Therefore, this research aims to examine the effectiveness of using Augmented Reality (AR)-based poster learning media to improve student learning outcomes in plant cell structure. The research method employed is a descriptive case study, utilizing a purposive sampling technique where the sample is determined based on specific considerations. The sample for this study consisted of 33 students from class VII C, selected because their average learning outcome scores were the lowest compared to other classes. The collected data were analyzed using descriptive methods by calculating the N-Gain Score. The research findings indicate that the N-Gain Score reached 0.7, categorized as a high increase. Additionally, the effectiveness of the learning media was measured by calculating the average score of student learning outcomes after the implementation of the AR-based poster learning media. The average student learning outcome score was 235, with an effectiveness rate of 89.07%, categorized as very effective. This indicates that the use of AR-based poster learning media can significantly enhance student learning outcomes. The implementation of this learning media not only helps students memorize the organelles of plant cells and their functions but also increases their interest and understanding of biological concepts.